Regulating Reproductive Genetics: A Review of American Bioethics Commissions and Comparison to the British Human Fertilisation and Embryology Authority - Riley, Margaret Foster; Merrill, Richard (Science and Technology Law Review, 2019)
Many people are now advocating expanded government regulation of research and clinical use of reproductive technologies. Although many of these technologies have been in use or anticipated for more than twenty-five years, and a number of bioethics commissions have considered regulation of them, efforts to develop broad national regulation have largely failed. This article examines the role that government institutions can play and have played in designing regulation of assisted reproduction and reproductive technologies. We review the history of national commissions as proponents and architects of regulation and explore how their structure, mission, and political placement have influenced their success or failure. We then compare the experience of the United States to that of Great Britain which established the Human Fertilization and Embryology Authority (HFEA) in 1990 and consider whether the HFEA might be a model for future regulation in the United States. We conclude that bioethics commissions can play an important role in formulating policy but they cannot create necessary political consensus if that consensus is lacking. Moreover, while the United States can glean important lessons from the British experience, the two countries’ political, legal, and medical cultures differ in ways that suggest importation of the British model would be difficult and perhaps unwise.